Remain Results of Network Retail Transactions: Potential Charity in Indonesia - Muhammad Al Faridho Awwal; Dewi Wahyu Setyo Rini (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
In the modern market or what is usually known as retail chains, most goods are sold with non-rounded price which creates price differences that cannot be translated into any physical value of printed money. The accumulated price differences are usually donated into charities which are managed by certain companies. However, it makes people worried about any indications of management overlap between charity donations and Corporate Social Responsibility (CSR) due to the intransparency of datas in terms of their financial managements.Not to mention, the unfair distribution of the donation money only resulted into donation receipients that are very centralized in some areas. Therefore, using conceptual research method with qualitative datas and strong references we try to observe this problem so that this uneasiness of the society about any overlap of CSR distribution and the charity money from consumers can be put into rest.